Sport Event Attendance as a Function of Education: Evidence from the Uk - Friedman-Rafael, J; Galvez-Silva, T (Routledge, 2017)
This article studies the role of education in the decision to attend sporting events. The overall objective is to verify whether more educated individuals are more likely to go to sports events than their less educated counterparts. If education socializes persons to focus on sports, it would then partially offset negative alternatives such as alcohol, drug abuse and unlawful behaviours, creating a positive externality. Sport events consumption is extensive, highlighting the potential economic importance of the sports-education externality. To establish the role of education in sport attendance, this article applies a probabilistic linear regression model to data from the UK. The econometric formulation associates sport event attendance in the left hand side with education in the right hand side, while controlling for the socioeconomic variables that are known to affect a consumer’s decision to go to a sport event: gender, age, income, employment status, children, marital status, and geographical location, among others. These findings add to a somewhat limited literature on both the effect of education on sports attendance and secondarily, on the impact of other socioeconomic variables on attendance. © 2017 Informa UK Limited, trading as Taylor & Francis Group.